(untitled) (Research, Society and Development, 2022)
Anxiety disorder causes fear, panic and feelings of dread and helplessness in people. They are usually caused by family history, environment, psychological constitution, or even a physical illness. With the COVID-19 Pandemic, the rate of people with anxiety disorder has increased significantly, for those who were unprepared in this critical period. In this sense, the general objective of this research is to analyze Anxiety Disorders during the COVID-19 pandemic in Brazil in 2020., in addition to verifying Anxiety Disorders during the COVID-19 pandemic in Brazil 2020. The research was guided by a bibliographic method of qualitative analysis, with data search on platforms such as Google academic, Periodicals and Scielo. Through the study, sudden changes were observed with isolation measures and other recurring factors in this pandemic, which could influence the increase in cases of anxious people considerably. Health in the physical and mental aspects suffered and suffers such an impact, as this pandemic scenario ended up bringing an imbalance to mental health, in addition to behavioral changes that indicate the growth of Anxiety Disorder.